“A Study on Investment preferences of working women in urban area special reference to Ernakulum District - Sudheer , Anjana; S, Devika.; Menon, Rashmi. J. (International Journal of Psychosocial Rehabilitation, 2020)
Investment helps in growing our fund. People now a days are widely involved in many different investment activities. Investments also helps in growth of an economy. In the earlier days only a few women had a source of income on their own.so, only a very few women were involved in investment activities. In the present-day’s world, women are well educated and most of them have a source of income on their own. But, unlike the men women undertake investment only on a small scale, their major investment avenues being gold and bank deposits. The investing decision of each differs based on their intention some are focused on high returns whereas others look for the security. This study deals with the investment preferences among women and factors that influences women for selecting the avenues from a sample size of 50 respondents by conducting survey through questionnaire in Ernakulam District, Kerala. The data has been analyzed through Chi- square test. This study explores the fact that the salaried women prefer safety and secured returns. The study also shows that age has a significant influence on investment preference.